Managerial Problems Confronted By Executive Chefs in Hotels - BIRDIR, Kemal; CANAKCI, Seda Derinalp (International Review of Management and Marketing, 2014)
The study was conducted to determine the managerial problems confronted by executive chefs working at 4 and 5-star hotels in Turkey. A survey developed by the researchers was employed as a data collection tool. Answers given by participants were analyzed using “T-test” and “ANOVA” analyses in order to determine whether there are significant differences of opinion on the subject (collated in answers to the survey questionnaire) amongst executive chefs, based on answers given by them (expressed as average figures) dependent upon such variables as their “Age”, “Gender”, “Educational Status” and “Star status of the hotel within which they worked.” The study results showed that the most important problem confronting executive chefs was “finding educated/trained kitchen personnel.” On the specific problem, “responsibility and authority is not clear within the kitchen,” there was a significant difference of opinion by the gender of the executive chefs. Moreover, there was a significant difference of opinion dependent upon the star status of the hotels within which the chefs worked on the problem of whether or not “the working hours of kitchen personnel were too long.” The findings suggest that there are important problems confronted by executive chefs. Moreover, male and female executive chefs have different opinions on the magnitudes of some specific problems. Whereas there are various reports and similar publications discussing problems faced by executive chefs, the present study is the first one in the literature that solely explore the managerial problems experienced at a kitchen context. Keywords: Hotel Managements; Kitchen Management; Administrative Problems in Kitchen Management. JEL Classifications: L2; M1